Causality of gut microbiome and hypertension: A bidirectional mendelian randomization study - Li, Yihui; Fu, Ru; Li, Ruixuan; Zeng, Jianwei; Liu, Tao; Li, Xiaogang; Jiang, Weihong (Frontiers in Cardiovascular Medicine, 2023)
Background & Aims The pathogenesis of hypertension involves a diverse range of genetic, environmental, hemodynamic, and more causative factors. Recent evidence points to an association between the gut microbiome and hypertension. Given that the microbiota is in part determined by host genetics, we used the two-sample Mendelian randomization (MR) analysis to address the bidirectional causal link between gut microbiota and hypertension. Methods We selected genetic variants (P < 1 × 10−5) for gut microbiota (n = 18,340) from the MiBioGen study. Genetic association estimates for hypertension were extracted from genome-wide association study (GWAS) summary statistics on 54,358 cases and 408,652 controls. Seven complementary MR methods were implemented, including the inverse-variance weighted (IVW) method, followed by sensitivity analyses to verify the robustness of the results. Reverse-direction MR analyses were further conducted to probe if there was a reverse causative relationship. Bidirectional MR analysis then examines a modulation of gut microbiota composition by hypertension. Results At the genus level, our MR estimates from gut microbiome to hypertension showed that there were 5 protective factors Allisonella, Parabacteroide, Phascolarctobacterium, Senegalimassilia, and unknowngenus (id.1000000073), while 6 genera Clostridiuminnocuum, Eubacteriumcoprostanoligenes, Eubacteriumfissicatena, Anaerostipes, LachnospiraceaeFCS020, and unknowngenus (id.2041) are risk factors. The Alcaligenaceae and ClostridialesvadinBB60 were detrimental and beneficial at the family level, respectively. In contrast, the MR results of hypertension-gut flora showed hypertensive states can lead to an increased abundance of Eubacteriumxylanophilum, Eisenbergiella, and Lachnospiraceae and a lower abundance of Alistipes, Bilophila, Butyricimonas, and Phascolarctobacterium. Conclusion Altered gut microbiota is a causal factor in the development of hypertension, and hypertension causes imbalances in the intestinal flora. Substantial research is still needed to find the key gut flora and explore the specific mechanisms of their effects so that new biomarkers can be found for blood pressure control.